Surgical outcomes of canalicular tear repair with self-retaining Mini-Monoka stent in a tertiary care hospital in Kashmir in North India - Birjees Hakak,; Junaid S Wani, (Asian Journal of Medical Sciences, 2022)
Background: Canalicular lacerations contribute to approximately 16% of the eye lid injuries. The torn medial end is to be identified, cut end sutured, and then the canaliculus intubated to restore patency. Silicone being inert, flexible, easily available, and cost effective is the material of choice for lacrimal stenting. Aims and Objectives: The aim of this study was to determine the surgical outcomes of the canalicular tear repair with the self-retaining Mini-Monoka stent in a tertiary care hospital in North India. Materials and Methods: Patients presenting to tertiary care hospital in Kashmir, North India with canalicular tear from August 2019 to December 2020 were included in this prospective study and repaired with self-retaining Mini-Monoka stent under microscope. All the patients were analyzed for demographic data, mode of injury, complications, and outcomes and followed up after a week, 6 weeks, and 3 months and stent removed after 6 weeks. Results: The study was conducted on 18 patients. The mean age of the patients was 37.5 years with male: female ratio of 5:1. The lower canaliculus was most commonly involved and road traffic accidents was the most common mode of injury (27.7%). The most common associated injury was lid injury (50%). The mean time of stent removal was 6 weeks±2 weeks. Syringing was done in all the patients except children. At last follow-up, 17 out of 18 patients had functional and anatomical success in terms of absence of epiphora and patent syringing and all the patients were cosmetically satisfied. Conclusion: Our study concludes that surgical repair of canalicular tear with Mini-Monoka stent is a safe and simple reliable technique, cosmetically satisfying with minimal manipulation giving high functional and anatomical success rate post repair.